Genç Yetişkinlerde Mutluluğa Genel Bir Bakış - Aydın, Merve (Muş Alparslan Üniversitesi, 2019)
Young adulthood is aperiod in which many personal and social changes are experienced, variouschallenges must be dealt with and challenging development tasks are faced. In this period, happiness during ensures  healthyidentity development of young people made it necessary to address happiness inyoung adults. The aim of this study is to examine the issue of happiness inyoung adults. The method of this study is reviving of literature. This studyincludes structure of happiness, importance of happiness, young adulthood anddevelopmental tasks, problems in young adulthood and research on happiness inyoung adults.

Gençyetişkinlik pek çok kişisel ve sosyal değişimin yaşandığı, çeşitli sorunlarlabaşa çıkılması gereken ve zorlayıcı gelişim görevleriyle karşı karşıya kalınanbir dönemdir. Bu dönemde mutluluğun gencin sağlıklı kimlik gelişiminin devamınısağlaması, genç yetişkinlerde mutluluğun ele alınmasını gerekli kılmıştır. Buçalışmanın amacı genç yetişkinlerde mutluluk konusunu incelemektir. Çalışmadaliteratür taramasına dayalı olarak mutluluk ve yapısı, mutluluğun önemi, gençyetişkinlik dönemi ve gelişim görevleri, genç yetişkinlikte yaşanan sorunlar vegenç yetişkinlerde mutluluk ile ilgili yapılan araştırmalar ele alınmıştır.
An Overview of the Happiness in the Young Adults
anemon
Keywords: Young Adult; Happiness; Subjective Well-Being; Genç Yetişkin; Mutluluk; Öznel İyi Oluş